Fungsi Budaya Cerita Rakyat dalam Upacara ‘Jembul Bedekah’ di Desa Banyumanis Donorojo Jepara - Laura Andri Retno (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Folklore serves to reveal about society, people's way of thinking.The folklore of Banyumanis Village Donorojo Jepara serves as entertainment for the supporting community. This story can provide a fun way to escape from the real world that is full of difficulties, thus turning something difficult into something more exciting. This study aims to determine the transmission process and the functions that appear in the folklore of Banyumanis Village. Through a qualitative descriptive approach with interview, observation and literature study techniques, it was found that folklore in addition to functioning as entertainment, education, reflection and ritual also provides awareness to the public about the past.